Qualität der Verkehrsinfrastruktur amerikanischer Metropolen. - Belzner, Heidrun; Bertini, Robert L.; Bogenberger, Klaus (Deutscher Verkehrs-Verl., 2009)
In der heutigen Zeit werden aufgrund zunehmender Verkehrsprobleme Fragen über die Qualität der Verkehrsinfrastruktur eines Landes oder eines Ballungsraumes, die verkehrlichen Wirkungen von Maßnahmen oder die generelle Entwicklung des Verkehrsgeschehens immer wichtiger. Eine kontinuierliche Auswertung ausgewählter verkehrlicher Kenngrößen und damit verbunden eine Bewertung der Verkehrsverhältnisse und der Verkehrsinfrastruktur würde einen Überblick über die zeitliche Entwicklung der Verkehrsverhältnisse eines Ballungsraumes erlauben.

The analysis covers 20 US metropolitan areas and their traffic results since 1982, and categorize systematically the transport infrastructure of these metropolitan areas. General trends are highlighted, while the research results for New York City, Chicago, Los Angeles and San Francisco are explained in detail. The "Urban Mobility Report" and the "Highway Performance Monitoring System" have served as a data basis for all the metropolitan areas. Traffic results are arranged in chronological order, going back to the first records of 1982. The main purpose of our research has been the evaluation of congestion levels, including their increases, in metropolitan areas, and of traffic-related delays for journeys by car within existing road networks. General trends and growth patterns in individual cases over given periods of time are deemed to be of special interest. A comparison or ranking of cities' overall traffic levels and of their infrastructure systems was not the primary objective of this research, since different criteria and constraints impose limits on further evaluation.
A comparison of US metropolitan areas' traffic and infrastructure systems.
Keywords: Verkehr; Stadtverkehr; Verdichtungsraum; Stadtregion; Bevölkerungsdichte; Straßenverkehr; Verkehrsinfrastruktur; Verkehrsentwicklung; Individualverkehr; Verkehrsmittelwahl; Leistungsfähigkeit; Leistungsvergleich; Verkehrsstatistik; Zersiedelung; Metropolregion; Verkehrsmanagement; Verkehrsträger; Verkehrsleistung; Kenngröße